Design and Evaluation of an AR Voice-based Indoor UAV Assistant for Smart Home Scenarios - Helmert, Robin; Hardes, Tobias; Yigitbas, Enes (Proceedings of the ACM Symposium on Spatial User Interaction (SUI 2023))
As technology advances, Unmanned Aerial Vehicles ( UAVs) have emerged as an innovative solution to a variety of problems in many fields. Automated control of UAVs is most common in large area operations, but they may also increase the versatility of smart home compositions by acting as a physical helper. For example, a voice- controlled UAV could act as an intelligent aerial assistant that can be seamlessly integrated into smart home systems. In this paper, we present a novel Augmented Reality (AR )-based UAV control that provides high-level control over a UAV by automating common UAV missions. In our work, we enable users to operate a small UAV hands-free using only a small set of voice commands. To help users identify the targets, and to understand the UAV ’s intentions, targets within the user’s field of vision are highlighted in an AR interface. We evaluate our approach in a user study (n=26) regarding usability, physical and mental demand, as well as a focus on the users’ preferences. Our study showed that the use of the proposed control was not only accepted, but some users stated that they would use such a system at home to help with some tasks at home

Entwicklungsprädiktoren fachdidaktischen Wissens zu digitalen Medien - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Riese, Josef; Weiler, David (Lernen, Lehren und Forschen in einer digital geprägten Welt. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Aachen 2022)

Erste Ergebnisse eines Seminars zur Förderung digitaler Kompetenzen - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Lernen, Lehren und Forschen in einer digital geprägten Welt. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Aachen 2022)

Entwicklung und Evaluation eines Fachpraktikums für das Lehramtsstudium Technik zur Förderung fachpraktischer Kompetenzen - Ermel, Dorothee Leonie
High-quality teacher education is the basis for high competences of future teachers. To prepare them adequately for the demands of their future teaching profession, it is essential to know (i) which subject-specific competences and skills they need and (ii) how these can be acquired in teacher education. However, empirical findings on necessary competences as well as on the design of teacher training courses are scarcely available on the subject of technology, since mainly general, normative recommendations on potential study contents exist. To fill this gap, this work focuses on the investigation of necessary practical competences of prospective technology teachers. The acquisition of such practical competences and skills is of great importance for the school subject of technology when, for example, machines are operated, tools are used, or objects are designed and manufactured. However, there is a lack of a differentiated description of the practical requirements for technology teachers and the teaching-learning processes required for this in the teacher training. The aim of this work is therefore the theory- and empirically-guided development and evaluation of a practical demand-oriented course for the technology teacher training programme at RWTH Aachen University to promote subject-specific practical competences. The development was structured as an iterative process by the Model of Educational Reconstruction (MER), according to which three major aspects were investigated and connected. (1) In a first step, the competences to be acquired were described and structured, taking normative perspectives into account as well as an empirical needs assessment among teachers and teacher educators to clarify and analyse the science subject matter. (2) In a second step, the student teacher´s perspective was surveyed to adapt the course to their initial competences, skills and experiences. (3) In a third step, the content and the didactic structure of the practical course was developed iteratively, considering the findings of the preceding steps and various requirements for the design and the tasks of the practical course (e.g., a necessary differentiation or a self-directed examination of the practical tasks in the course). The practical course was taught in several runs and evaluated with respect to the perceived learning outcomes of the student teachers as well as to the quality of the course. The evaluation was carried out through self-assessment of the students in a questionnaire and a written portfolio. The findings of the evaluation indicate a positive perception regarding the quality of the course. The students positively assessed the course structure (e.g., sequence of the course contents) and individual course elements (e.g., concrete course tasks). Furthermore, an increase in practical competences and skills – regardless of initial experience – was found. The work provides groundwork for further studies, for example on the level of competence acquisition or the long-term effect of the practical course.

Schreibimpulse in sprachlichen Lernprozessen - Drepper, Laura; Herrmann, Franziska; Nußbaum, Alena (Schreibunterricht. Studien und Diskurse zum Verschriften und Vertexten)

Rechtschreibfehler - Drepper, Laura (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK) Online)

Erzählen zu fantastischen Bildern. Kinder sprechen über Formen und Funktionen grammatischer Mittel in Erzählu - Drepper, Laura (Die Grundschulzeitschrift)

Rechtschreibanalyse - Drepper, Laura (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK) Online)

Rechtschreibregel - Drepper, Laura (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK))

Quellen und Flüsse in den Monumenta. Zum Natur- und Umweltbewusstsein eines Barockfürsten - Ströhmer, Michael (Monumenta. Erinnerungsorte zwischen Weser und Lippe. Die Monumenta Paderbornsensia des Ferdinand von Fürstenberg)

Leben an den Quellen. Europäische Wasserkultur entlang der Pader

'Pappeln, die grüne Messer sind' und 'ratlose Brillenbären in Zoo'. Deformierte Naturverhältnisse bei Angela Krauß und Herta Müller - Morrien, Rita (Werke im Dialog. (Virtuelle) Begegnungen anlässlich von 40 Jahren Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller)

Prekäre Existenzen - Geschlecht, Klasse, Ethnizität und Körper in Christian Petzolds "Jerichow" (2008) und Visar Morinas "Exil" (2020) - Morrien, Rita (Interkulturelle Konstellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann)

Droste Lab - Geschlecht #2 - Morrien, Rita; Gfrereis, Heike; Seifert, Nicole (Mit den Gespenstern leben. (Haunting/Heritage))

Transatlantisches Nachwirken - Annette von Droste-Hülshoff und Cindy Sherman im 'Cross-Mapping'-Verfahren - Morrien, Rita (Droste Jahrbuch 14)

Aquatische Relektüre: Christian Petzolds "Undine" erklärt Berlin und geht - Morrien, Rita (Weimarer Beiträge)

Wissenschaftsbezogener Rechtspopulismus/-extremismus an Hochschulen – Perspektiven von Betroffenen - Haker, Christoph; Otterspeer, Lukas (ZRex – Zeitschrift für Rechtsextremismusforschung)
Mit dem Begriff wissenschaftsbezogener Rechtspopulismus/-extremismus fokussiert der Beitrag solche (extrem) rechten Organisationen, Praktiken und Diskursstrategien, die sich auf das Feld der Wissenschaft beziehen. Dabei rückt in einer qualitativen Interview-Studie die Betroffenenperspektive in den Mittelpunkt, die ein blinder Fleck der Forschung ist: Wie nehmen Betroffene wissenschaftsbezogenen Rechtspopulismus/-extremismus wahr und welche Umgangsweisen finden sie? Präsentiert werden Ergebnisse zur widersprüchlichen Erscheinungsform von wissenschaftsbezogenem Rechtspopulismus/-extremismus. Neben erwartbaren Phänomenen (zum Beispiel (kultur-)rassistischen, misogynen, antidemokratischen und verschwörungstheoretischen Positionierungen) zeigt sich dieser insofern widersprüchlich, als dass er zwischen Inanspruchnahme von Wissenschaftlichkeit sowie Wissenschaftsfreiheit auf der einen Seite und Wissenschaftsfeindlichkeit auf der anderen Seite oszilliert. Er trifft mit Hochschulen auf Institutionen, deren Strukturen einen kritischen Umgang erschweren, und er wirkt weit über die jeweils konkreten Situationen seines Erscheinens hinaus. Unsere Analysen untermauern die Notwendigkeit, die Bedeutung von wissenschaftsbezogenem Rechtspopulismus/-extremismus in seiner Widersprüchlichkeit über die jeweiligen Situationen hinaus zu erkennen und wissenschaftsspezifische Antworten zu finden, die dieser Widersprüchlichkeit Rechnung tragen – und sind damit eine Aufforderung an Hochschulen und alle dort tätigen Personen.

Meromorphic Continuation of Weighted Zeta Functions on Open Hyperbolic Systems - Schütte, Philipp; Weich, Tobias; Barkhofen, Sonja (Communications in Mathematical Physics)
In this article we prove meromorphic continuation of weighted zeta functions in the framework of open hyperbolic systems by using the meromorphically continued restricted resolvent of Dyatlov and Guillarmou (2016). We obtain a residue formula proving equality between residues of weighted zetas and invariant Ruelle distributions. We combine this equality with results of Guillarmou, Hilgert and Weich (2021) in order to relate the residues to Patterson-Sullivan distributions. Finally we provide proof-of-principle results concerning the numerical calculation of invariant Ruelle distributions for 3-disc scattering systems.

Invariant Ruelle Distributions on Convex-Cocompact Hyperbolic Surfaces -- A Numerical Algorithm via Weighted Zeta Functions - Schütte, Philipp; Weich, Tobias (arXiv:2308.13463)
We present a numerical algorithm for the computation of invariant Ruelle distributions on convex co-compact hyperbolic surfaces. This is achieved by exploiting the connection between invariant Ruelle distributions and residues of meromorphically continued weighted zeta functions established by the authors together with Barkhofen (2021). To make this applicable for numerics we express the weighted zeta as the logarithmic derivative of a suitable parameter dependent Fredholm determinant similar to Borthwick (2014). As an additional difficulty our transfer operator has to include a contracting direction which we account for with techniques developed by Rugh (1992). We achieve a further improvement in convergence speed for our algorithm in the case of surfaces with additional symmetries by proving and applying a symmetry reduction of weighted zeta functions.

Editorial: Bildungsbezogener Rechtspopulismus/-extremismus - Haker, Christoph; Otterspeer, Lukas; Rödel, Severin Sales (ZSE Zeitschrift für Soziologie der Erziehung und Sozialisation)

Einladung zum Draußen-Bleiben. Safer Spaces sind nicht nur Schutzraum, sie sind eine Methode der Herrschafts- und Erkenntniskritik. - Haker, Christoph; Otterspeer, Lukas; Thole, Werner

Wie hältst du es mit der Wahrheit? Bilder von Wissenschaft und Wissenschaftler*in-Sein angesichts von Diagnosen der Postfaktizität. - Haker, Christoph; Otterspeer, Lukas (Entgrenzungen. Beiträge zum 28. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft)

Gegen eine Militarisierung des Pädagogischen. Über die Folgen des Ukraine-Kriegs für die politische Bildung - Haker, Christoph; Otterspeer, Lukas (Ungewissheit als Erfahrung in der Demokratie)

Wissenschaftsbezogener Rechtspopulismus/-extremismus. Eine Podiumsdiskussion. - Haker, Christoph; Lehnert, Esther; Otterspeer, Lukas; Thole, Werner (Polarisierte Welten. Verhandlungen des 41. Kongresses der Deutschen Gesellschaft für Soziologie in Bielefeld 2022)

Wissenschaftsbezogener Rechtspopulismus/-extremismus an Hochschulen - eine Feldexploration und Herausforderungen in der Lehre - Haker, Christoph; Otterspeer, Lukas (ZSE Zeitschrift für Soziologie der Erziehung und Sozialisation)

Einfluss von Prozessparametern auf Dreiblech-Hybrid-Mischverbindungen beim zweistufigen Widerstandselementschweißen - Haak, Viktor; Yang, Keke; Meschut, Gerson (13. Fügetechnisches Gemeinschaftskolloquium)

Europa erfahren, begreifen, vermitteln. Ansätze zur Entwicklung einer synkritischen Europadidaktik - Schreckenberg, Stefan; Marchetti, Andreas (Europa im Fremdsprachenunterricht)

Herkunftsbedingte und sprachliche Einflüsse bei der häuslichen Internetnutzung von Kindern - Richter, Lea; Gruchel, Nicole; Buhl, Heike M.; Kamin, Anna-Maria (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Der Beitrag betrachtet die digitale häusliche Lernumwelt von Kindern unter besonderer Berücksichtigung der Differenzkategorien Herkunft und Sprache und erarbeitet Zusammenhänge zwischen dem Migrationshintergrund, der Familiensprache, einer internetbezogenen Eltern-Kind-Interaktion sowie einer unterhaltungs- und schulbezogenen Nutzung des Internets von Kindern. Empirische Grundlagen sind standardisierte Eltern- und Kinderbefragungen sowie ethnografisch orientierte Untersuchungen in Familien. Die quantitativen Analysen zeigen, dass Kinder, deren Hauptverkehrssprache in der Familie nicht Deutsch ist, häufiger gemeinsam mit ihren Eltern das Internet nutzten. Vertiefend liessen in der qualitativen Untersuchung diejenigen Kinder häufigere und komplexere Internetnutzungsformen für schulische Zwecke erkennen, die einen Migrationshintergrund aufweisen und hauptsächlich in ihrer Herkunftssprache (nicht Deutsch) innerhalb der Familie sprechen. Insbesondere in Familien, die selten in der Häuslichkeit Deutsch sprechen, hat sich die (gemeinsame) Internetrecherche als Mittel zur Kompensation von Sprachbarrieren erwiesen. Fehlende elterliche Unterstützungsmöglichkeiten aufgrund von sprachlichen Verständnisproblemen können insofern durch kindliche, elterliche oder gemeinsame Rechercheprozesse ausgeglichen werden.
Keywords: General Medicine

Bounds for the chromatic index of signed multigraphs - Steffen, Eckhard; Wolf, Isaak Hieronymus (Discrete Applied Mathematics)
Keywords: Applied Mathematics; Discrete Mathematics and Combinatorics

Das Scheitern Ulrichs von Hutten. Fiktion und Funktion einer ritterlichen Selbstbeschreibung - Moritz, Tilman (Ebernburg-Hefte)

Decision Support Ecosystems: Assisted Low-Code Development of Tailored Decision Support Systems - Kirchhoff, Jonas
Erfolg und Misserfolg eines Unternehmens werden maßgeblich durch getroffene Entscheidungen beeinflusst. Daher verlassen sich Entscheider oft auf Entscheidungsunterstützungssysteme, die durch Datensimulation, -optimierung und -visualisierung bei der Identifizierung von geeigneten Entscheidungen unterstützen. Für eine optimale Unterstützung muss ein Entscheidungsunterstützungssystem (EUS) jedoch auf den Entscheidungsprozess eines Entscheiders abgestimmt sein und verfügbare Daten, Optimierungsziele, persönliche Präferenzen sowie weitere Einflussfaktoren berücksichtigen. EUS-Entwickler können aufgrund der Komplexität und Volatilität von Geschäftsumgebungen allerdings nicht alle potenziellen Entscheidungsprozesse während des Entwurfs eines EUS vorhersehen, wodurch ein EUS einem Entscheider häufig nur unzureichende Anpassungsmöglichkeiten an den individuellen Entscheidungsprozess bietet. Die Einzelanfertigung eines EUS, das auf einen Entscheidungsprozess zugeschnitten ist, ist ein kosten- und zeitintensives Unterfangen aufgrund der begrenzten Verfügbarkeit von Softwareentwicklern oder Missverständnissen zwischen Entwicklern und Entscheidern während der Entwicklung. Daher geben sich Entscheider möglicherweise mit einem handelsüblichen EUS zufrieden, das nicht vollständig mit ihrem Entscheidungsprozess übereinstimmt, suboptimale Entscheidungen begünstigt und so den Unternehmenserfolg negativ beeinflusst. In dieser Arbeit wird ein Ansatz vorgeschlagen, der es Entscheidern ermöglicht, selbst maßgeschneiderte Entscheidungsunterstützungssysteme zu entwickeln und so die Diskrepanz zwischen benötigter und tatsächlicher Entscheidungsunterstützung zu vermeiden. Dazu stellen EUS-Entwickler einen Teil der EUS-Funktionalität als wiederverwendbare Software-Dienste bereit ...

Graph-Theoretical Models for the Analysis and Design of Socio-Technical Networks - Cappello, Chiara; Steffen, Eckhard (The Digital Twin of Humans)

Rotation r-graphs - Steffen, Eckhard; Wolf, Isaak Hieronymus (Discrete Mathematics)
Keywords: Discrete Mathematics and Combinatorics; Theoretical Computer Science

On Lieb-Robinson bounds for a class of continuum fermions - Hinrichs, Benjamin; Lemm, Marius; Siebert, Oliver (arXiv:2310.17736)
We consider the quantum dynamics of a many-fermion system in $\mathbb R^d$ with an ultraviolet regularized pair interaction as previously studied in [M. Gebert, B. Nachtergaele, J. Reschke, and R. Sims, Ann. Henri Poincar\'e 21.11 (2020)]. We provide a Lieb-Robinson bound under substantially relaxed assumptions on the potentials. We also improve the associated one-body Lieb-Robinson bound on $L^2$-overlaps to an almost ballistic one (i.e., an almost linear light cone) under the same relaxed assumptions. Applications include the existence of the infinite-volume dynamics and clustering of ground states in the presence of a spectral gap. We also develop a fermionic continuum notion of conditional expectation and use it to approximate time-evolved fermionic observables by local ones, which opens the door to other applications of the Lieb-Robinson bounds.

A Lower Bound on the Critical Momentum of an Impurity in a Bose-Einstein Condensate - Hinrichs, Benjamin; Lampart, Jonas (arXiv:2311.05361)
In the Bogoliubov-Fr\"ohlich model, we prove that an impurity immersed in a Bose-Einstein condensate forms a stable quasi-particle when the total momentum is less than its mass times the speed of sound. The system thus exhibits superfluid behavior, as this quasi-particle does not experience friction. We do not assume any infrared or ultraviolet regularization of the model, which contains massless excitations and point-like interactions.

Higher rank quantum-classical correspondence - Hilgert, Joachim; Weich, Tobias; Wolf, Lasse Lennart (Analysis & PDE)
For a compact Riemannian locally symmetric space $Γ\backslash G/K$ of arbitrary rank we determine the location of certain Ruelle-Taylor resonances for the Weyl chamber action. We provide a Weyl-lower bound on an appropriate counting function for the Ruelle-Taylor resonances and establish a spectral gap which is uniform in $Γ$ if $G/K$ is irreducible of higher rank. This is achieved by proving a quantum-classical correspondence, i.e. a 1:1-correspondence between horocyclically invariant Ruelle-Taylor resonant states and joint eigenfunctions of the algebra of invariant differential operators on $G/K$.

Spectral correspondences for finite graphs without dead ends - Bux, Kai-Uwe; Hilgert, Joachim; Weich, Tobias (arXiv:2307.10876)
We compare the spectral properties of two kinds of linear operators characterizing the (classical) geodesic flow and its quantization on connected locally finite graphs without dead ends. The first kind are transfer operators acting on vector spaces associated with the set of non backtracking paths in the graphs. The second kind of operators are averaging operators acting on vector spaces associated with the space of vertices of the graph. The choice of vector spaces reflects regularity properties. Our main results are correspondences between classical and quantum spectral objects as well as some automatic regularity properties for eigenfunctions of transfer operators.

Spectral correspondences for rank one locally symmetric spaces: the case of exceptional parameters - Arends, Christian; Hilgert, Joachim (Journal de l’École polytechnique — Mathématiques)
In this paper we complete the program of relating the Laplace spectrum for rank one compact locally symmetric spaces with the first band Ruelle-Pollicott resonances of the geodesic flow on its sphere bundle. This program was started by Flaminio and Forni for hyperbolic surfaces, continued by Dyatlov, Faure and Guillarmou for real hyperbolic spaces and by Guillarmou, Hilgert and Weich for general rank one spaces. Except for the case of hyperbolic surfaces a countable set of exceptional spectral parameters always left untreated since the corresponding Poisson transforms are neither injective nor surjective. We use vector valued Poisson transforms to treat also the exceptional spectral parameters. For surfaces the exceptional spectral parameters lead to discrete series representations of $SL(2,\mathbb R)$. In higher dimensions the situation is more complicated, but can be described completely.
Keywords: Ruelle resonances; Poisson transforms; locally symmetric spaces; principal series representations

Spectral correspondences for rank one locally symmetric spaces - The case of exceptional parameters - Hilgert, Joachim; Arends, C. (J. de l'École polytechnique — Mathématiques)

Aspects of control theory on infinite-dimensional Lie groups and G-manifolds - Hilgert, Joachim; Glöckner, H. (J. Diff. Equations)

Open Educational Resources zur Förderung nachhaltiger Bildung und Forschung. In: Jahrestagung 2023 der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaften - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. The Teacher-Training-Platform on the SAFE Project Website - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. Administrative and financial information - Schneider, Jennifer Nicole

Green-4-Future – Project Insights to its best! In: Training and Cooperation Activity (TCA) “Green Erasmus: pathways to sustainable projects and institutions” - Schneider, Jennifer Nicole

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA1. Business CANVAS Model – in Green Entrepreneurships - Schneider, Jennifer Nicole

Game Studies – Role Play in Therapy and Education. Pen and Paper Congress.Vortrag: Potenziale von Open Educational Resources bei Pen& Paper Rollenspielen in der Bildungspraxis nutzen! – Warum und wie soll das gehen?! - Schneider, Jennifer Nicole

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA2. Creative Thinking – in Green Entrepreneurships - Schneider, Jennifer Nicole

STEMinAction- Final Project Meeting – Unlocking Long-Term Sustainability: Harnessing Open Educational Resources (OER) Beyond Project Lifetimes - Schneider, Jennifer Nicole

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA1. Use, sharing and creating Open Educational Resources – Why is it so important? - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. The SAFE Learning Videos - Schneider, Jennifer Nicole